LONG-TERM MONITORING USER VASECTOMY SURGERY IN THE NATIONAL HOSPITAL CAYETANO HEREDIA - Untiveros, Fernando (2015)
OBJECTIVE: To know the side effects of vasectomy and acceptance of the user population by this method. DESIGN: Descriptive study. MATERIALS AND METHODS: 50 patients were included vasectomy users between February 1997 and September 1998 at the National Hospital Cayetano Heredia. Release 7.5 (November 14, 1996) as standard - for statistical analysis SPSS for Windows was used. RESULTS: Side effects occurred in 8% of the users of this method. Acceptance of this family planning method was 94% of users. In patients who experienced side effects, 6% had infection and inflammation of the surgical wound and 2% mild pain in one of the testicles. In 6% of users, where vasectomy was not well received, 2 patients (4%) had at the beginning of a new pregnancy by their partner at 8 and 14 months, respectively, after the procedure. One patient (2%) reported having had a postoperative very badly run. CONCLUSION: Vasectomy, as a method of family planning, appears to be widely accepted because it has few side effects.